Analisis Perbandingan Agenda Setting Media Cetak dan Media Radio di Mandailing Natal : Studi Kasus Malintang Pos dan Radio StartFM - Farid, Ahmad Salman (Communication and Islamic Broadcasting Studies IAIN Parepare, 2023)
This study aims to analyze the comparative agenda setting between print media and radio in Mandailing Natal Regency, with a case study focusing on two main local media outlets, namely Malintang Pos and Radio StartFM. Agenda setting is a crucial process in the field of journalism as it influences the public's attention to specific issues. The research adopts a qualitative approach, employing content analysis to identify differences and similarities in how news is handled by the two media platforms. The findings of the study reveal that print media, such as Malintang Pos, tend to provide more in-depth and sharp coverage of local issues. Conversely, Radio StartFM tends to deliver concise and oral news, prioritizing speed in disseminating information to its listeners. The process of agenda setting in both media is influenced by factors such as political interests, economic pressures, and editorial preferences, which impact the selection of news topics. Furthermore, the variation in the medium of news delivery also influences the format and writing style of the news presented. Despite these differences, both print media and radio play significant roles in shaping public opinion and societal perception regarding local issues. This research contributes conceptually to understanding the roles of print media and radio in providing information to the public. The implications of these findings are expected to provide valuable insights for journalism practitioners, academics, and readers, encouraging critical analysis of news presented by both media outlets. Moreover, this study can serve as a basis for further research in the context of media agenda setting in other regions.